A novel piezostack-driven jetting dispenser with corner-filleted flexure hinge and high-frequency performance. (11th April 2018) - Bu, Zhenxiang; Lin, Siying; Huang, Xiang; Li, Anlin; Wu, Dezhi; Zhao, Yang; Luo, Zhiwei; Wang, Lingyun
Abstract: This paper presents a new jetting dispenser which is applicable to high-frequency microelectronic packaging. In order to achieve high frequency glue jetting and improve the stability of jetting dispensers, we redesign a novel displacement amplifying mechanism, and a new on–off valve jetting dispenser driven by piezoelectric actuators is developed. Firstly, the core part of this jetting dispenser—the displacement amplifying mechanism with a corner-filleted flexure hinge—is proposed and a comparison with the previous structure is carried out; then the characteristic dimensional parameters of the amplifying mechanism are determined by theoretical calculation and finite element analysis. Secondly, a prototype of the dispenser with the displacement amplifying mechanism is fabricated based on the determined parameters. We use a laser displacement sensor to test the displacement of the needle, and a maximum amplifying displacement output of 367 µ m is obtained under an applied 200 V to the piezoelectric actuator, which is consistent with the simulation result and meets the requirement of high displacement output. Thirdly, we build an integrated testing system. Mixed glycerol/ethanol is chosen as the experimental dispensing glue, and the experiment and analysis of a droplet diameter are conducted. A higher jetting frequency of 400 Hz and a smaller droplet diameter of 525 µ m are achieved with the glycerol/ethanol mixture, and the characteristics of consistency and temperature influencing the droplet diameter are verified by experiments.